Drought Evolution in the Srepok River Basin (2000-2022) Based on the Vegetation Health Index (VHI) and Standardized Precipitation Index (SPI) - Cong Luc, Huynh; Viet, Luong Van (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 1, 2025)
This study aims to evaluate drought dynamics using the Vegetation Health Index (VHI) in the Srepok River Basin during the period 2000–2022 and to analyze the relationship between meteorological drought and vegetation condition. The Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST) data derived from MODIS satellite imagery were utilized to calculate the VHI, while rainfall data from meteorological stations were employed to compute the Standardized Precipitation Index (SPI). The analysis shows that VHI exhibits the strongest correlation with SPI at a 6-month scale (SPI6), particularly in April, marking the end of the dry season. During the 23-year study period, drought events demonstrated a recurrence pattern of approximately 3–5 years, with severe episodes occurring in 2005 and 2016, coinciding with strong El Niño events. Spatial analysis indicates that the northwestern middle and lower sub-basins were most severely affected, with drought durations exceeding six months and frequencies greater than 14%. Crop-specific assessment shows that annual crops and rice were the most drought-sensitive groups, while perennial crops exhibited higher drought tolerance but still sustained significant damage due to their extensive cultivation area. These findings underscore the effectiveness of integrating VHI and SPI6 as tools for agricultural drought monitoring and early warning in the region.